Analisis Tingkat Pemborosan Waktu Pelayanan Poli Mata Dengan Value Stream Mapping Dan Value Stream Analysis Pada RSU Muhammadiyah Ponorogo - Yupiya Dwi Nur Ariska; Enny Aryanny (Fakultas Teknik Universitas Cenderawasih, 2023)
Muhammadiyah Ponorogo General Hospital is one of the private hospitals in Ponorogo Regency. At this time the Muhammadiyah Ponorogo General Hospital has received Plenary accreditation from the Indonesian Hospital Accreditation Institute (LARSI). The problem that is often faced by hospitals is that there is a lot of waste that occurs in the service process at the Eye Polyclinic of RSU Muhammadiyah Ponorogo. The most critical level of waste for eye polyclinic services is waiting with a weighting value of 4.00, waste inventory with a value of 3.16, waste overproduction with a weighting value of 3.00, waste defects with a weighting value of 2.91 , waste inappropriate processing with a weight value of 2.66, waste unnecessary motion with a weight value of 2.58, waste transportation with a weight value of 1.41, and waste underutilized abilities of people with a weight value of 2.25. The initial activity time before the repair was 14,677 seconds or 244 minutes (4 hours) and after the repair was reduced to 6,577 seconds or 109 minutes (1 hour 61 minutes). The highest waste is waiting, namely doctors often do not come on time and there is a lack of nurses or pharmacists in the pharmacy with a Risk Priority Number (RPN) score of 252 and 224. Recommendations for improvement that can be proposed are adding doctors to the eye poly department to reduce doctor delays because there are surgery schedules that often collide with the schedule for opening eye poly services and adding medical personnel to the pharmacy department, to reduce queues you can use a drug delivery application that can be accessed by patients without having to queue again at the hospital.